Dietary effects on multi-element composition of European eel (Anguilla anguilla) otoliths - Marohn, Lasse; Prigge, Enno; Zumholz, Karsten; Klügel, Andreas; Anders, Heike; Hanel, Reinhold (Marine Biology, 2009)
Otolith microchemistry is widely used as a tool to track individual migration pathways of diadromous fish under the assumption that the elemental composition of fish otoliths is directly influenced by the physicochemical properties of the surrounding water. Nevertheless, several endogenous factors are reported to affect element incorporation into fish otoliths and might lead to misinterpretations of migration studies. This study experimentally examined the influence of eight different diets on the microchemical composition of European eel (Anguilla anguilla) otoliths using laser ablation inductively coupled plasma mass spectrometry (LA-ICP-MS). Seven natural prey types and one artificial diet were fed during 8 weeks in freshwater circuits. Results show for the first time that food has no significant influence on the incorporation of Na, Sr, Ba, Mg, Mn, Cu and Y into European eel otoliths. This indicates that the incorporation of elements usually chosen for migration studies is not affected by diet and that individual feeding behaviour of A. anguilla will not lead to any misinterpretation of migration pathways.